2021
DOI: 10.1021/acs.organomet.1c00364
|View full text |Cite
|
Sign up to set email alerts
|

Gold-to-Boron Aryl Transfer from a T-Shaped Phosphine–Borane Gold(I) Complex

Abstract: T-shaped gold­(I) complexes with significant Au→B interactions were prepared from the phosphine–borane i-Pr2P­(o-C6H4)­BFXyl2 [Fxyl = 3,5-(F3C)2C6H3]. The (P,B)­AuArF complex 4 [ArF = 4-(F3C)­C6H4] was obtained by an indirect route involving ligand exchange from (ArO)3PAuArF 3a [Ar = 2,4-(t-Bu)2C6H3]. A different outcome was observed with the analogous precursor (MeO)3PAuArF 3b. Here, the phosphite remains bonded to gold, and the borane moiety abstracts the ArF group from gold to give the zwitterionic dicoordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…For this study, i Pr 2 P­( o -C 6 H 4 )­BFxyl 2 (Fxyl = 3,5-(F 3 C) 2 C 6 H 3 ) 1-Fxyl was chosen as a phosphine-borane since we recently found that it readily reacts with organo (vinyl, alkynyl, aryl) Au­(I) complexes to give zwitterionic species . The possibility for 1-Fxyl to trigger reductive elimination was assessed with the μ-Cl bridged dimer (AuMe 2 Cl) 2 2 , which is reluctant to undergo C­(sp 3 )–C­(sp 3 ) coupling (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…For this study, i Pr 2 P­( o -C 6 H 4 )­BFxyl 2 (Fxyl = 3,5-(F 3 C) 2 C 6 H 3 ) 1-Fxyl was chosen as a phosphine-borane since we recently found that it readily reacts with organo (vinyl, alkynyl, aryl) Au­(I) complexes to give zwitterionic species . The possibility for 1-Fxyl to trigger reductive elimination was assessed with the μ-Cl bridged dimer (AuMe 2 Cl) 2 2 , which is reluctant to undergo C­(sp 3 )–C­(sp 3 ) coupling (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…[40] Concerning "tetrel bonding", in 2019, Gabbaï reported complexes 12 presenting a phosphane ligand incorporating a xanthylium or acridinium unit. [41] The carbenium center, possessing an empty p x orbital with lower energy than an analogous borane fragment, [42] has the potential to serve as a more robust σ-acceptor ligand for gold, thereby overall enhancing the electrophilicity of the metal center. Similarly, the authors hypothesize a substrate push/carbenium pull working mode to elucidate the activity observed in the cyclization of propargylbenzamides.…”
Section: Triel Tetrel Pnictogen and Chalcogen Bondingmentioning
confidence: 99%
“…Recently, we have started to explore the impact of phosphine-boranes on gold chemistry and discovered some unique features, namely facile organic group transfer between boron and gold( i ) 3 and Lewis acid-assisted C(sp 3 )–C(sp 3 ) coupling at gold( iii ). 4 Here, we investigated the possibility of activating acyl chlorides at gold thanks to the use of phosphine-borane ligands.…”
Section: Introductionmentioning
confidence: 99%